2012
DOI: 10.1099/jmm.0.037234-0
|View full text |Cite
|
Sign up to set email alerts
|

Colicin insensitivity correlates with a higher prevalence of extraintestinal virulence factors among Escherichia coli isolates from skin and soft-tissue infections

Abstract: Colicins are toxic proteins with a narrow killing spectrum that are produced by colicinogenic Escherichia coli strains. The aim of this study was to analyse systematically whether extraintestinal virulence potential is linked to colicin (in)sensitivity. In total, 102 well-characterized E. coli isolates from skin and soft-tissue infections (SSTIs) were exposed to 17 single-colicinproducing strains, and the correlation between insensitivity to colicin and phylogenetic group as well as the extra-intestinal virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…At the same time, several studies have shown an association between the production of some types of bacteriocins and pathogenic E. coli strains [20-23]. Previous studies have found that genes encoding colicin E1, as well as microcins H47, M, I47, E492 and V were associated with extraintestinal pathogenic E. coli strains [20-23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, several studies have shown an association between the production of some types of bacteriocins and pathogenic E. coli strains [20-23]. Previous studies have found that genes encoding colicin E1, as well as microcins H47, M, I47, E492 and V were associated with extraintestinal pathogenic E. coli strains [20-23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that genes encoding colicin E1, as well as microcins H47, M, I47, E492 and V were associated with extraintestinal pathogenic E. coli strains [20-23]. Colicin E1 is also known to have toxic effects on eukaryotic cells and is considered to be a virulence factor in UPEC strains [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have published similar findings, looking at the relationship of microcins and bacteriocin synthesis with VFs in human disease. [12][13][14] The blaTEM findings from the following article examined antibiotic resistance gene expression and found that in their population blaTEM was associated with increased risk of severe sepsis.…”
mentioning
confidence: 99%
“…These antimicrobial peptides or proteins are diverse and widespread among Gram-positive and Gram-negative bacteria [11]. It is becoming evident that they are linked to pathogenesis as they play a role in displacing bacterial flora, enhancing colonization and therefore infection ( [11][12][13] and Sharp et al unpublished data). In fact, protein bacteriocin-encoding genes can be found in the genomes of most Gram-negative pathogens, including P. aeruginosa, E. coli and K. pneumoniae ( [14] and Sharp et al unpublished data).…”
Section: Introductionmentioning
confidence: 99%